Functional links between thermoregulation and sleep in children with neurodevelopmental and chronic health conditions - McCabe, Susan M.; Abbiss, Chris R.; Libert, Jean-Pierre; Bach, Véronique (Frontiers in Psychiatry, 2022)
The bi-directional relationship between sleep and vigilance is recognised to be important for all children. It is particularly consequential for children who have neurodevelopmental disorders or health conditions which challenge their sleep and biological rhythms, and their ability to maintain rhythms of participation in activities in everyday life. There are many studies which report the diverse reasons for disruption to sleep and vigilance in these populations. Predominantly, there is focus on respiratory, pharmaceutical, and behavioural approaches to management. There is, however, little exploration and explanation of the important effects of body thermoregulation on children’s sleep-wake patterns, and associated behaviours. Circadian patterns of sleep-wake are dependent on patterns of body temperature change, large enough to induce sleep preparedness but remaining within the everyday circadian range to avoid sleep disturbances when active thermoregulatory responses against heat or cold are elicited (for thermoneutrality maintenance). Additionally, the subjective notion of thermal comfort (which coincides with the objective concept of thermoneutrality) is of interest as part of general comfort and associated behavioural responses for sleep onset and maintenance. Children’s thermoregulation and thermal comfort are affected by diverse biological functions, as well as their participation in everyday activities, within their everyday environments. Hence, the aforementioned populations are additionally vulnerable to disruption of their thermoregulatory system and their capacity for balance of sleep and vigilance. Translational information provides a hitherto overlooked opportunity for consideration of assessment and intervention strategies to support children’s thermoregulation functions, promote their subjective thermal comfort and in turn improve regulation of sleep and vigilance.